2013
DOI: 10.1155/2013/915953
|View full text |Cite
|
Sign up to set email alerts
|

Artemisia iwayomogiExtract Attenuates High-Fat Diet-Induced Obesity by Decreasing the Expression of Genes Associated with Adipogenesis in Mice

Abstract: The objective of the present study was to determine whether Artemisia iwayomogi (AI) extract reduces visceral fat accumulation and obesity-related biomarkers in mice fed a high-fat diet (HFD), and if so, whether these effects are exerted by modulation of the expression of genes associated with adipogenesis and inflammation. AI extract supplementation for 11 weeks significantly prevented HFD-induced increments in body weight, visceral adiposity, adipocyte hypertrophy, and plasma levels of lipids and leptin. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 49 publications
0
20
0
1
Order By: Relevance
“…Obesity is associated with type II diabetes, hypertension and coronary heart disease [2,22,23]. Sulforaphane is involved in the inhibition of adipogenesis and can reduce the risk of cardiovascular disease [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated with type II diabetes, hypertension and coronary heart disease [2,22,23]. Sulforaphane is involved in the inhibition of adipogenesis and can reduce the risk of cardiovascular disease [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…A hepatoprotective effect of A. iwayomogi extract was reported in rodent models with different types of liver diseases, such as alcoholic fatty liver [ 9 ], carbon tetrachloride-induced chronic hepatic fibrosis [ 10 , 11 ], and cholestatic liver fibrosis [ 12 ]. We previously reported that A. iwayomogi extract (0.5% w / w diet) reduced visceral fat accumulation and obesity-related biomarkers in mice fed a HFD by modulating the expression of genes associated with adipogenesis and inflammation in adipose tissues [ 13 ]. Concurrently in this extract-fed mice, we also observed a decrease in plasma TG levels, however the underlying mechanism responsible was not elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The aerial parts of AI have been used in traditional medicine to treat various infectious diseases including hepatitis, cholecystitis, carbuncles, and jaundice [9,10]. In particular, AI extracts have shown hepatoprotective effect in animal liver disease models including fatty liver and liver fibrosis [11,12]. Furthermore, a previous study reported that the essential oil isolated from AI induces epidermoid carcinoma cell apoptosis [13].…”
mentioning
confidence: 99%